Tricky integration!

Calculus Level 4

3 3 x 8 { x 11 } d x = ? \int_{-3}^3 x^8 \{ x^{11} \} \, dx = \, ?


Notation: { } \{ \cdot \} denotes the fractional part function , { x } = x x \{ x\} = x- \lfloor x \rfloor .

59049 6561 19683 2187

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
May 13, 2017

I = 3 3 x 8 { x 11 } d x = 3 3 x 8 ( x 11 x 11 ) d x = 3 3 x 19 d x 3 3 x 8 x 11 d x Note that x 19 is odd. = 0 3 0 x 8 x 11 d x 0 3 x 8 x 11 d x Replace x with x = 0 3 x 8 x 11 d x 0 3 x 8 x 11 d x = 0 3 x 8 ( x 11 + x 11 ) d x Note that x + x = 1 for non-integer x = 0 3 x 8 d x = x 9 9 0 3 = 2187 \begin{aligned} I & = \int_{-3}^3 x^8\left \{x^{11}\right \} dx \\ & = \int_{-3}^3 x^8\left( x^{11} - \left \lfloor x^{11} \right \rfloor \right) dx \\ & = {\color{#3D99F6} \int_{-3}^3 x^{19} dx} - \int_{-3}^3 x^8 \left \lfloor x^{11} \right \rfloor dx & \small \color{#3D99F6} \text{Note that } x^{19} \text{ is odd.} \\ & = {\color{#3D99F6} 0} - {\color{#D61F06} \int_{-3}^0 x^8 \left \lfloor x^{11} \right \rfloor dx} - \int_0^3 x^8 \left \lfloor x^{11} \right \rfloor dx & \small \color{#D61F06} \text{Replace }x \text{ with }-x \\ & = - {\color{#D61F06} \int_0^3 x^8 \left \lfloor -x^{11} \right \rfloor dx} - \int_0^3 x^8 \left \lfloor x^{11} \right \rfloor dx \\ & = - \int_0^3 x^8 \left({\color{#3D99F6}\left \lfloor -x^{11} \right \rfloor + \left \lfloor x^{11} \right \rfloor} \right) dx & \small \color{#3D99F6} \text{Note that } \lfloor x \rfloor + \lfloor -x \rfloor = - 1 \text{ for non-integer} x \\ & = \int_0^3 x^8 \ dx = \frac {x^9}9 \ \bigg|_0^3 = \boxed{2187} \end{aligned}

Rohit Sharma
May 12, 2017

You have to use two properties here . One of integration and other of fractional part. a b f ( x ) d x \displaystyle\int_{a}^{b}f(x) {\,dx} = a b f ( a + b x ) d x \displaystyle\int_{a}^{b}f(a+b-x) {\,dx} and

x \langle x \rangle + + x \langle -x \rangle = = 1

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...